DIPG-64. REST MODULATES NEOVASCULATURE VIA REGULATION OF GREMLIN EXPRESSION IN DIFFUSE INTRINSIC PONTINE GLIOMA. Issue 2 (22nd June 2018) - Shaik, Shavali; Kennis, Bridget; Maegawa, Shinji; Schadler, Keri; Yanwen, Yang; Callegari, Keri; Lulla, Rishi; Goldman, Stewart; Nazarian, Javad; Rajaram, Veena; Fangusaro, Jason; Gopalakrishnan, Vidya
Abstract: Children with diffuse intrinsic pontine glioma (DIPG) have an extremely poor survival. This underscores the desperate need for novel, biology-driven therapies. Here, we investigated the involvement of RE1 Silencing Transcription Factor (REST), a chromatin remodeler and regulator of brain development, in DIPG pathology. We discovered that when compared to normal controls, REST protein is significantly elevated in DIPG patient samples with H3K27M mutation. Compared to isogenic DIPG cell lines with endogenous REST expression, cells engineered to express higher levels of human REST transgene exhibited enhanced tumor growth. Surprisingly, REST elevation also caused an increase in tumor vasculature. In vitro, REST loss in DIPG cells caused a decrease in tube formation by human umbilical vein endothelial cells (HUVECs) and human brain microvascular endothelial cells (HBMECs), indicating that REST regulates the DIPG microenvironment. Mechanistically, we identified a bone morphogenic factor (BMP) signaling antagonist and ligand for VEGFR2, Gremlin-1 (GREM-1), as a downstream effector of REST-dependent changes in tumor vasculature. REST-dependent GREM-1 secretion promoted activation of AKT signaling in HUVECs and HBMECs. VEGFA-C levels were not significantly altered between normal and H3K27M mutant DIPGs and did not correlate with REST expression. In summary, our study is the first to demonstrate both tumor intrinsic and tumor extrinsic functions for REST in DIPG. The latter is of particular significance because it opens the door for re-evaluation of anti-angiogenic therapies targeting GREM-1, in DIPGs with REST elevation, possibly in combination with standard of care.